Exploring cultural differences in wildlife value orientations using student samples in seven nations - Maarten H Jacobs; Sara Dubois; Tetsuro Hosaka; Vukan Ladanović; Huda Farhana Mohamad Muslim; Kelly K. Miller; Shinya Numata; E. Ranaweerage; Tanja M. Straka; Michael A. Weston; Zulkhairi Azizi Zainal Abidin (Biodiversity and Conservation, 2022)
Understanding differences in the way people think about wildlife across countries is important as many conservation challenges transcend jurisdictions. We explored differences in wildlife value orientations in seven countries: Australia, Canada, Germany, Japan, Malaysia, the Netherlands and Serbia. Standard scales assessed domination (prioritizing human well-being) and mutualism (striving for egalitarian relationships with wildlife). We used student samples (total n = 2176) for cross-cultural comparisons. Reliabilities of the wildlife value orientations scales were adequate in all countries. Relationships between demographics and wildlife value orientations were different across countries. Men were generally more oriented towards domination and less towards mutualism than women, except in Serbia, where it was the other way around. Estimated at the level of the individual (using ANOVA), wildlife value orientations varied across countries, with nationality explaining a larger portion of the variation in mutualism (21%) than domination (6%). Estimated at the level of countries (using multilevel modelling), effect sizes were comparable. Thought about wildlife has previously only been examined within single countries. This paper makes a new contribution to the conservation literature suggesting that wildlife value orientations vary by country, and are associated with demographic factors. For conservation practices, understanding national differences in the way people think about wildlife is crucial to understanding sources of conflict among practitioners. Such knowledge is also important to gain public support for conservation.

Suitability of Wild Boar (Sus scrofa) as a Bioindicator for Environmental Pollution with Perfluorooctanoic Acid (PFOA) and Perfluorooctanesulfonic Acid (PFOS) - J. Kowalczyk; J. Numata; B. Zimmermann; R. Klinger; F. Habedank; P. Just; H. Schafft; M. Lahrssen-Wiederholt (Archives of Environmental Contamination and Toxicology, 2018)

Effects of different silvicultural systems on the genetic diversity of Shorea parvifolia populations in the tropical rainforest of Southeast Asia - Widiyatno; S. Indrioko; M. Na’iem; K. Uchiyama; S. Numata; M. Ohtani; A. Matsumoto; Y. Tsumura (Tree Genetics & Genomes, 2016)

Carbazole angular dioxygenation and mineralization by bacteria isolated from hydrocarbon-contaminated tropical African soil - L. B. Salam; M. O. Ilori; O. O. Amund; M. Numata; T. Horisaki; H. Nojiri (Environmental Science and Pollution Research, 2014)

The responses of leaf litter ant communities to wildfires in the Brazilian Amazon: a multi-region assessment - Juliana M. Silveira; Jos Barlow; Rafael B. Andrade; Júlio Louzada; Luiz A. Mestre; Sébastien Lacau; Ronald Zanetti; Izaya Numata; Mark A. Cochrane (Biodiversity and Conservation, 2013)

Does the trace element composition of brown trout Salmo trutta eggs remain unchanged in spawning redds? - R. M. Gabrielsson; J. Kim; M. R. Reid; C. H. Stirling; M. Numata; G. P. Closs (Journal of Fish Biology, 2012)
The temporal stability of trace element concentrations in fertilized, artificially incubated anadromous brown trout Salmo trutta eggs and newly hatched fry was investigated. The anadromous status of the parental fish was confirmed using strontium isotopic analysis of otoliths. Whilst manganese concentrations in eggs varied over time, concentrations of aluminium, potassium, magnesium, strontium, barium and calcium were all unchanged 1 week and 6 weeks post‐fertilization as well as in recently hatched larvae. The results clearly suggest that the distinctive trace element signature present in the eggs and newly hatched larvae of anadromous S. trutta (typically characterized by high strontium, low barium) is stable over time. Therefore analysis of the trace element composition of eggs is concluded to be a cost‐effective and reliable method for determining the spatial and temporal extent of upstream spawning migration by anadromous salmonids. The temporal variability of at least one element in this study suggests the stability of untested multi‐element signatures cannot automatically be assumed.

Crystal structure and mode of action of a class V chitinase from Nicotiana tabacum - Takayuki Ohnuma; Tomoyuki Numata; Takuo Osawa; Mamiko Mizuhara; Kjell M. Vårum; Tamo Fukamizo (Plant Molecular Biology, 2011)

Characterization of single L-type Ca2+ channels in myocytes isolated from the cricket lateral oviduct - T. Numata; M. Yoshino (Journal of Comparative Physiology B, 2005)

Effects of ER-34122, a novel dual 5-lipoxygenase/cyclooxygenase inhibitor, on indices of early articular lesion in MRL/MpJ-lpr/lpr mice - T. Horizoe; N. Nagakura; K. Chiba; H. Shirota; M. Shinoda; H. Numata; S. Kobayashi; C. Abe (Inflammation Research, 1999)

ER-34122, a novel dual 5-lipoxygenase/cyclooxygenase inhibitor with potent anti-inflammatory activity in an arachidonic acid-induced ear inflammation model - T. Horizoe; N. Nagakura; K. Chiba; H. Shirota; M. Shinoda; N. Kobayashi; H. Numata; Y. Okamoto; S. Kobayashi (Inflammation Research, 1998)

Molecular characterization of morphologically typical human calicivirus Sapporo - K. Numata; M. E. Hardy; S. Nakata; S. Chiba; M. K. Estes (Archives of Virology, 1997)

Dot blot hybridization with a cDNA probe derived from the human calicivirus Sapporo 1982 strain - K. Kogawa; S. Nakata; S. Ukae; N. Adachi; K. Numata; D. O. Matson; M. K. Estes; S. Chiba (Archives of Virology, 1996)